栄養表示の活用と学習ニーズ - 遠藤 和子; 谷口 千絵 (日本看護研究学会雑誌, 2004)
This study was conducted in the visitors at the open seminar "Our Diet and Health" and the parents of preschool children for two purposes: １. To expose a picture of their interests in and use of nutrition labels as well as problems. ２. To understand what they want to know and how they can learn. The results showed that 90% of the subjects used of nutrition labels. They made the most of the labeling of processed foods and vacuum-packed foods in the visitors group, and snack foods followed by drinks in the parents group. In the ingredients shown in the labels, they paid the most attention to sodium and then fat in the visitors group, calorie, calcium, and then sugar in the parents group. We believe that these differences were due to the difference of the health issues between the groups. Both groups required the labels because of the lack of prior knowledge about the recommended dietary allowances and the ingredients that meet their health requirements at the current stage in their lifecycle, and also the environmental factors when shopping. Therefore, they have needs for continuous learning, in which we believe specialists such as healthcare professionals need to be involved. 本研究の目的は，「食生活と健康を考える」展の公開講座参加者と，幼稚園児の保護者を対象に，１.栄養表示に対する関心および活用の実態と問題点を明らかにし，２.栄養表示についての学習ニーズとして知りたい情報や学習の方法について把握することである。方法は自記式質問紙を用い，回収率は66.８%であった。結果は，対象者の９割が栄養表示を活用していた。表示を参考にする食品は，公開講座参加者が加工食品･レトルト食品，園児保護者では市販菓子，飲料の順である。栄養成分は，公開講座参加者はエネルギー，塩分，脂質の順であり，園児保護者はエネルギー，カルシウム，糖質の順に多い。この違いは，抱える健康問題によると考えられた。栄養表示が活かせない理由は，ライフサイクルに応じた所要量と健康問題に関する栄養成分の知識不足，買い物時の環境要因にあった。このため継続した学習へのニーズがあり，保健・医療職など専門家の介入が重要であると考えられた。